2023
DOI: 10.1002/ppp3.10371
|View full text |Cite
|
Sign up to set email alerts
|

How to reconcile renewable energy and agricultural production in a drying world

Abstract: Societal Impact StatementRenewable energies such as photovoltaics can mitigate climate change by replacing fossil fuels, but they will compete with other forms of land use when implemented in open space. Agrivoltaics provide a promising approach to reconciling food and energy needs by allowing for agricultural and electrical power production on the same area of land. Agrivoltaics have a high potential to attenuate negative effects of drought on crop growth and, thus, can help to increase resilience of agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Utility-scale solar energy deployment, however, competes with food production and often reduces biodiversity (Allardyce et al, 2017;Barron-Gafford et al, 2016;Böhm et al, 2022). In this context, AV reduces the competition for land resources and with thoughtful management can enhance biodiversity compared with PV alone (Amaducci et al, 2018;Barron-Gafford et al, 2019;Feuerbacher et al, 2021;Laub et al, 2022;Schweiger & Pataczek, 2023;Weselek, Bauerle, Hartung, et al, 2021). Further, AV consistently increases the efficiency of land use or land productivity with an average land equivalent ratio (LER).…”
Section: Challenges and Potential Benefits Of Agrivoltaics: Balancing...mentioning
confidence: 99%
“…Utility-scale solar energy deployment, however, competes with food production and often reduces biodiversity (Allardyce et al, 2017;Barron-Gafford et al, 2016;Böhm et al, 2022). In this context, AV reduces the competition for land resources and with thoughtful management can enhance biodiversity compared with PV alone (Amaducci et al, 2018;Barron-Gafford et al, 2019;Feuerbacher et al, 2021;Laub et al, 2022;Schweiger & Pataczek, 2023;Weselek, Bauerle, Hartung, et al, 2021). Further, AV consistently increases the efficiency of land use or land productivity with an average land equivalent ratio (LER).…”
Section: Challenges and Potential Benefits Of Agrivoltaics: Balancing...mentioning
confidence: 99%
“…Furthermore, careful consideration must be given to the panel-induced heterogeneity of the moisture distribution in the soil, an aspect that requires further investigations since it is typically a strong predictor of productivity [22]. In terms of evapotranspiration, a reduction in atmospheric water demand has recently been reported, even in years with low precipitation [62]. Similarly, a model evaluation for arid and semi-arid environments predicted a reduction in crop water consumption by 30-40% for static arrays with a 50% shading rate [63].…”
Section: Microclimatic Conditions Under the Panelsmentioning
confidence: 99%
“…In terms of food production, SAS could offer advantages for certain crops harvested for leaves, stems, or roots [28]. For example, studies have confirmed that the shade cast by PV panels can increase edible biomass production in chicory and lettuce [20,21,31].…”
Section: Introductionmentioning
confidence: 99%